Afanassjewa en Einstein. Wederzijdse waardering - van der Heijden, Margriet (Studium, 2016)
Afanassjewa and EinsteinIn 1912 Tatiana Afanassjewa (1876–1964), a Russian mathematician, arrived in Leiden. The university in this city had an amazingly flourishing physics department. Afanassjewa accompanied her husband Paul Ehrenfest (1880–1933), a theoretical physicist from Vienna, who was to become successor to the famous professor Hendrik Antoon Lorentz. Soon the couple’s house became a regular meeting place for Dutch mathematicians and physicists, and a temporary home for many learned guests from all over the world. Among them was Albert Einstein, a close friend of Ehrenfest, with whom he shared a passion for physics and music. This paper recapitulates their friendship and includes new details about Afanassjewa, who was to initiate a fierce debate on the didactics of mathematics in The Netherlands and whose sharp and analytical mind made an impression on Einstein. Both the Ehrenfest-Afanassjewa couple and Einstein had a vivid interest in international relations and, the role of science therein. Afanassjewa and Einstein stayed in touch through letters and cards after Ehrenfest’s untimely death in 1933, the year when Hitler rose to power in Germany and Einstein moved to the United States.